Assia Djebar : out of Algeria - Hiddleston, Jane (Contemporary French and francophone cultures ;, 2006)
For more than fifty years, Assia Djebar, Silver Chair of French at New York University and winner of the Neustadt Prize for Contribution to World Literature, has used the tools of poetry, fiction, drama and film to vividly portray the world of Muslim women in all its complexity. In the process, she has become one of the most important figures in North African literature. In Assia Djebar, Jane Hiddleston traces Djebar's development as a writer against the backdrop of North Africa?s tumultuous history.